Geotechnical Properties of Lateritic Soil Stabilized with Ground-Nut Husk Ash - Emeka Segun Nnochiri; Olumide Moses Ogundipe (Salehan Institute of Higher Education, 2016)
This study assesses the geotechnical properties of lateritic soil stabilized with Ground-nut Husk Ash. Preliminary tests were carried out on the natural soil sample for identification and classification purposes, while consistency limits tests were thereafter carried out as well. Engineering property tests such as California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS) and compaction tests were performed on both the natural soil sample and the stabilized lateritic soil, which was stabilized by adding Ground-nut Husk Ash, GHA, in percentages of 2, 4, 6, 8 and 10 by weight of the soil. The results showed that the addition of GHA enhanced the strength of the soil sample. The Maximum Dry Density (MDD) reduced from 1960 kg/m3 to 1760 kg/m3 at 10% GHA by weight of soil. The Optimum Moisture Content (OMC) increased from 12.70% to 14.95%, also at 10% GHA by weight of soil. The unsoaked CBR values increased from 24.42% to 72.88% finally, the UCS values increased from 510.25 kN/m2 to 1186.46 kN/m2, for both CBR and UCS, the values were at 10% GHA by weight of soil. It was therefore concluded that GHA performs satisfactorily as a cheap stabilizing agent for stabilizing lateritic soil especially for subgrade and sub base purposes in road construction.